Local ecological knowledge in toponyms in the Waduk Jatigede area: An anthropological linguistic study - Sari, Dini Gilang; Suhandano, Suhandano (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
Toponyms or place names are important linguistic facts. Toponyms can record people's spatial awareness of the surrounding environment. This article explores local ecological knowledge in toponyms in the Waduk Jatigede area. In this area, there are 28 villages from 5 sub-districts affected by the construction of Waduk Jatigede. Data collection in this study used participant observation and interview methods. The data analysis procedure includes four stages: (1) transcription of recorded data; (2) categorizing data from the transcription of recordings or notes based on the classification of toponymy aspects; (3) interpretation of local knowledge about ecology in toponymy; (4) concluding. The results show that polymorphemic toponyms dominate toponyms in the Jatigede Reservoir area. In addition, toponyms in the Waduk Jatigede area are also dominated by toponyms with physical aspects, including hydrological, geomorphological, and biological-ecological characteristics. This finding shows that Sundanese people have a close relationship with the surrounding nature. This local ecological knowledge contains Sundanese people's ecological awareness about the Waduk Jatigede area's ecological characteristics, including water, soil, flora and fauna. This local ecological knowledge is useful as a policy recommendation for natural and ecological disaster mitigation in environmental development, which is essential for achieving the Sustainable Development Goals (SDGs).